EKSPLORASI TEKNIK PENGERITINGAN VERTIKAL DALAM PENATAAN RAMBUT DESAIN MODERN DI SALON KECANTIKAN - Neguita Pinem, Igrelatercia; Simanjuntak, Ivolyne; Salsabila, Alya; Ramadhani, Syifa; Rezki Fauzani, Asrah; Putri, Mutia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore in-depth the vertical perming technique in modern hair styling design, including conceptual understanding, implementation procedures, and its application in beauty salons. The research method uses a qualitative approach with a literature study type that examines various sources, including scientific journals, theses, and research articles related to hair perming. The object of study is focused on the practice of vertical perming applied in beauty salons as part of professional hair styling services. Data analysis techniques use content analysis with stages of data reduction, data presentation, and conclusion drawing. The results show that vertical perming is a hair rolling technique with the roller positioned perpendicularly following the direction of hair fall, producing elongated, soft, and natural curls. The implementation procedure includes preparation stages, hair diagnosis, washing, hair parting, vertical rolling, solution application, perming process, rinsing, neutralization, and finishing. The success factors of this technique are determined by the accuracy of roller selection, hair health conditions, and the technical mastery of the hairstylist. This study concludes that the vertical perming technique is an essential competency in hair beauty because it can create natural and voluminous curl designs according to the client's facial characteristics.